2014
DOI: 10.3109/1547691x.2014.885619
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects ofPteridium aquilinumenhance susceptibility to urethane-induced lung carcinogenesis

Abstract: Pteridium aquilinum (bracken fern), one of the most important toxic plants in the world, contains the toxic norsequiterpene ptaquiloside that induces cancers in humans and farm animals. Previous studies in the laboratory demonstrated immunotoxic effects produced by ptaquiloside, which are characterized by suppression of natural killer (NK) cell activity (i.e. cytotoxicity and interferon [IFN]-production). However, it is unknown whether these immunosuppressive effects could contribute to carcinogenesis in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Figure 4 shows representative histological microphotographs as a function of scan timepoint for the histological analysis (LC) subgroup, and at 5 months for the NC group. Precancerous lesions classified as alveolar epithelial hyperplasia were observed at 1 month after urethane injection [ 22 ]. This was followed by a mixture of alveolar epithelial hyperplasia and atypical adenomatous hyperplasia at 2 months, and adenoma at 3 and 5 months.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows representative histological microphotographs as a function of scan timepoint for the histological analysis (LC) subgroup, and at 5 months for the NC group. Precancerous lesions classified as alveolar epithelial hyperplasia were observed at 1 month after urethane injection [ 22 ]. This was followed by a mixture of alveolar epithelial hyperplasia and atypical adenomatous hyperplasia at 2 months, and adenoma at 3 and 5 months.…”
Section: Resultsmentioning
confidence: 99%
“…Ptaquiloside is a DNA-alkylating agent, which causes point mutations, as well as structural and numeric chromosomal aberrations [ 19 , 20 , 21 ]. This toxin also has immunotoxic properties, contributing to reducing immune surveillance against newly arising neoplasms [ 22 , 23 , 24 ]. Other ferns containing ptaquiloside (e.g., Pteris spp.…”
Section: Prevalence and Aetiologymentioning
confidence: 99%
“…Viruses, such as papillomavirus, might act as co-carcinogens [13]. In addition, ptaquiloside likely has an immunotoxic effect, as experimental studies with mice reported repression of the cytotoxic activity of natural killer cells [14,15]. However, ptaquiloside levels have not yet been determined in P. arachnoideum.…”
Section: Introductionmentioning
confidence: 99%